A hybrid sectional moment projection method for modeling soot particle dynamics in laminar premixed flames. (1st January 2023) - Zhang, Zhixuan; Han, Xu; Wang, Mingda; Wu, Zhengjie; Sun, Xiang; Wu, Shaohua
Abstract: In this work, a new and robust numerical approach for solving the population balance equations that describe the soot particle dynamics in laminar premixed flames is presented. The new approach is a combination of fixed sectional method and moment projection method, hence the name hybrid sectional moment projection method. It adopts a number of quadrature nodes within each section to describe the complex soot particle interactions. The positions of some quadrature nodes are specially assigned to achieve a better statistical representation of the particle population. The performance of this new approach is first tested using a simplified population balance model under a homogeneous condition, then it is implemented into the PREMIX/OPPDIF code packages to simulate the soot particle dynamics in two sooting reference flames. Results suggest that this new approach is much superior to the conventional fixed sectional method in terms of numerical accuracy and computational efficiency. The evolutions of the particle global quantities as well as the detailed size distribution could be well captured by the new approach using very few sections. Highlights: A new solution algorithm for handling the soot population balance model is presented. This new method has advantages of high convergence rate and prediction accuracy. This method enables a comprehensive analysis into the soot evolution process.